2016
DOI: 10.26719/2016.22.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of invasive Neisseria meningit idis strains isolated at the Children's Hospital of Tunis, Tunisia

Abstract: Neisseria meningitidis, a leading cause of bacterial meningitis and other serious infections, is responsible for approximately one-third of cases of bacterial meningitis in the Children's Hospital of Tunis. The serogroup distribution, antibiotic susceptibility and antigenic and molecular characteristics of N. meningitidis isolates were determined in patients aged 3 days-13 years between February 1998 and June 2013. In all 107 invasive strains of N. meningitidis were isolated. Reduced susceptibility to penicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
5
18
0
Order By: Relevance
“…Our data showed that the majority of the isolates were of serogroup B, in agreement with a previous report (13). Recent data from Tunisia also suggested that serogroup B predominated in the country between 1998 and 2013 (23). Serogroup B isolates were also reported in Algeria between 1992 and 2001 (24).…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that the majority of the isolates were of serogroup B, in agreement with a previous report (13). Recent data from Tunisia also suggested that serogroup B predominated in the country between 1998 and 2013 (23). Serogroup B isolates were also reported in Algeria between 1992 and 2001 (24).…”
Section: Discussionsupporting
confidence: 92%
“…Surveillance data indicated that the incidence and prevalence of Nm serogroups continually varies both geographically and temporally [23,24]. Currently, meningococcal serogroup B (MenB) is a major cause of IMD in North America, South America, Australia, North Africa, and Europe, although a decreasing incidence trend is being observed [25], which was supported by the data presented from other countries at the 2018 GMI meeting [10,11,[26][27][28][29][30]. The incidence and prevalence of MenB naturally fluctuates over time and is currently at an all-time low; the reasons for this were unknown, but it was hypothesized that the introduction of a smoking ban in public places in some countries may have played a role.…”
Section: Serogroup Distributionmentioning
confidence: 83%
“…Finally, we note the presence of three cases of serogroup Y with a first appearance in 2013 in the Casablanca region [17]. In the Maghreb region, Meningococcal serogroup B represents 80.4 % of cases in Tunisia [18], moreover, in Algeria it represents 46.7 % of cases between 2003 and 2013 [19]. Serogroup B predominates in Europe, North America and Australia [3].…”
Section: Discussionmentioning
confidence: 98%
“…Thus at the national level, 10 % of the isolates are of serogroup C [24]. This figure remains much lower than that of Tunisia where serogroup C represents 12.2 % [18], 8 % in Algeria [19], 26 % in France [21], 50 % in Portugal [22] and 61 % in Switzerland [31].…”
Section: Discussionmentioning
confidence: 99%